Occurrence and treatment of peripheral nerve injuries after cosmetic surgeries - Chen, Qiang; Li, Pengfei; Zhao, QingFang; Tu, Tian; Lu, Hui; Zhang, Wei (Frontiers in Neurology, 2023)
Although non-invasive and minimally invasive aesthetic procedures increasingly dominate the cosmetic market, traditional plastic surgery remains the most effective improvement method. One of the most common complications in plastic surgery, peripheral nerve injuries, though has a low incidence but intrigued plastic surgeons globally.In this article, a narrative review was conducted using several databases (PubMed, EMBASE, Scopus, and Web of Science) to identify peripheral nerve injuries following cosmetic surgeries such as blepharoplasty, rhinoplasty, rhytidectomy, breast surgeries, and abdominoplasty. Surgery-related nerve injuries were discussed, respectively. Despite the low incidence, cosmetic plastic surgeries can cause iatrogenic peripheral nerve injuries that require special attention. The postoperative algorithm approaches can be effective, but the waiting and treatment processes can be long and painful. Preventive measures are undoubtedly more effective than postoperative remedies. The best means of preventing disease is having a good understanding of anatomy and conducting a careful dissection.